Management skills and their reflection in the settlement of insurance compensation: Applied Study in National Insurance Company and Iraqi Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The environment contemporary works for the insurance companies have seen a number of technological developments and changes rapidly in light of the intense competition in the insurance market, and this affects human behavior in the workplace, and to director in his work needs to be a set of managerial skills. so we find compensation activity in companies insurance needs a high managerial skills, so that compensation, director of the settlement procedure successfully. So research aims to test two hypotheses two major belongings variables search using some statistical methods to extract the results and interpretation and analysis (such as arithmetic mean, standard deviation, percentages, Alpha Cronbach's coefficient, Pearson correlation coefficient, simple regression coefficient) and use a program (EXCEL) and software (SPSS). The researcher found a correlation between the moral and the effect of variables presidents relationship, and the researcher in the end a number of recommendations to the two research sample based on the findings.